Adaptive control of a high-order buck-boost dc-dc converter - Chia, Chun Kiat (2017)
This report presents the implementation of a high-order buck-boost converter system. The controllers for the regulation of the buck-boost converter are also implemented. The controllers implemented are the current-mode controllers and the sliding-mode controllers. Experimental results to show the performances of the controllers under different operating conditions are presented and evaluated.